2012
DOI: 10.4103/0973-6131.91714
|View full text |Cite
|
Sign up to set email alerts
|

The effect of yoga in stress reduction for dental students performing their first periodontal surgery: A randomized controlled study

Abstract: Context:The dental students experience a lot of stress, which increase when they perform their first surgical procedure. Yoga as an anxiolytic tool in anxiety reduction has been practiced over centuries in India.Aim:To assess the efficacy of yoga in reducing the state trait anxiety of dental students before their first periodontal surgery performance.Settings and Design:A randomized controlled study using a two-way split plot design (pre-post-test) was conducted in the department of periodontics, Pacific Denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 26 publications
(32 reference statements)
4
45
0
2
Order By: Relevance
“…Dental students experience stress more often than the general population 4 and with greater intensity (distress) 7 , directly affecting their health and performance. However, there is little information about the strategies used to cope with stress and whether these are adequate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental students experience stress more often than the general population 4 and with greater intensity (distress) 7 , directly affecting their health and performance. However, there is little information about the strategies used to cope with stress and whether these are adequate.…”
Section: Discussionmentioning
confidence: 99%
“…The use of therapies to control stress was addressed with four dichotomous questions (Yes/No), considering the last 6 months. Questions were asked by the researchers according to 4 Data collection was conducted in person through the application of questionnaires.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Dental students suffer more stress than the rest of the population. 4 It has been reported that the largest increases of stress levels in dental students are associated with transitions between basic science, the preclinical level, and the clinical level, 5 with the most significant increase of stress starting in the clinical years. 6 Other conditions associated with stress in this population are depression, anxiety, substance abuse, decreased work efficiency, and burnout syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Yoga is an ancient science established in India which gives the practitioner not only a sound body but also a sound mindand has shown to have effects on most physiological systems of the body. 7,8 It is known to modulate autonomic output and helps achieve and maintain autonomic balance between two components (sympathetic and parasympathetic) of autonomic nervous system and stress. 9 This study is designed to demonstrate the presence of stress, anxiety in first year medical students and associated with altered heart variability, and the role of yoga as an effective intervention to reduce stress, anxiety and improve HRV.…”
Section: Introductionmentioning
confidence: 99%